Effect of shape of single-roll rapid solidification nozzles on properties of ribbons for magnesium rechargeable batteries - TABATA, Hironobu; HAGA, Toshio; AIDA, Tetsuo; KIRIMOTO, Yuichi; KURIHARA, Hideki; SUZUKI, Mayumi; TSUKEDA, Tadayoshi (Journal of Japan Institute of Light Metals, 2025)
In developing ribbons for use as anode materials in innovative rechargeable batteries, magnesium ribbons were manufactured using a single-roll rapid solidification method. The quality of ribbons, such as their surface characteristics and defects, was considered to be largely determined by the manufacturing conditions of single-roll rapid solidification method, and it was also reported that shape of nozzle used to spray molten magnesium also had a significant effect on the quality of ribbons. In this study, ribbons were produced using nozzles with various internal gradient angles, and the surface properties, cross-sectional structure, and internal and external defects of the ribbons were evaluated. In actual ribbon production, it was confirmed that a nozzle with a smaller gradient angle could produce ribbons with a stable yield of over 70%. This is because adding a gradient shape allows smooth molten metal to be sprayed out. In the microstructure observation of the ribbons, a network-like second phase was observed near the free-solidification surface. A difference in cell size was also confirmed with the change in nozzle shape. In addition, the relationship between cell size and hardness was investigated, and it was confirmed that the hardness value decreases as the cell size increases.